Collaborative sharing of multidimensional space-time data in a next generation hydrologic information system. (July 2020) - Gan, Tian; Tarboton, David G.; Horsburgh, Jeffery S.; Dash, Pabitra; Idaszak, Ray; Yi, Hong
Abstract: In hydrologic research, there is a need to manage, archive, and publish data in a discoverable way to increase data reuse, transparency, and reproducibility. Multidimensional space-time data are commonly used in hydrologic research, and systems are needed for sharing and exchanging such data. Simply exchanging files may result in loss of metadata information and can be challenging when files are large. We developed an approach to manage, share, and publish multidimensional space-time data in HydroShare, a next generation hydrologic information system and domain specific repository. This paper presents the design, development, and testing of this approach. We selected the Network Common Data Form (NetCDF) as the underlying data model. We defined specific metadata elements to store and manage multidimensional space-time data. We adopted and adapted existing software to automatically harvest, support entry of metadata, and establish standardized data services to serve and enhance access to the datasets shared in HydroShare. Highlights: Development of a framework for sharing multidimensional space-time data. Automatic harvesting of metadata to support data discovery and reuse. Easy to use metadata editing to add additional or missing information. Supports standard data services for programmatic access and subsetting. Users can share data through data services without requiring server setup.